2007
DOI: 10.1098/rstb.2007.2067
|View full text |Cite
|
Sign up to set email alerts
|

Structural analyses of a hypothetical minimal metabolism

Abstract: By integrating data from comparative genomics and large-scale deletion studies, we previously proposed a minimal gene set comprising 206 protein-coding genes. To evaluate the consistency of the metabolism encoded by such a minimal genome, we have carried out a series of computational analyses. Firstly, the topology of the minimal metabolism was compared with that of the reconstructed networks from natural bacterial genomes. Secondly, the robustness of the metabolic network was evaluated by simulated mutagenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 44 publications
4
46
0
Order By: Relevance
“…This may be the reason, for example, that development is slow; complex programs, executed slowly, lead to a more robust outcome than simple processes proceeding quickly. Conversely, simulations of minimal metabolic networks suggest that they are more fragile than naturally evolved ones (Gabaldó n et al 2007). As engineered systems begin to achieve complexity comparable to biological ones, explorations of the tradeoff between complexity and robustness in natural and engineered biological systems may have lessons to teach engineers of complex mechanical and electronic systems too.…”
Section: Resultsmentioning
confidence: 99%
“…This may be the reason, for example, that development is slow; complex programs, executed slowly, lead to a more robust outcome than simple processes proceeding quickly. Conversely, simulations of minimal metabolic networks suggest that they are more fragile than naturally evolved ones (Gabaldó n et al 2007). As engineered systems begin to achieve complexity comparable to biological ones, explorations of the tradeoff between complexity and robustness in natural and engineered biological systems may have lessons to teach engineers of complex mechanical and electronic systems too.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, genome-scale metabolic models exist that can be used to predict the set of metabolic functions required for a minimal organism to be viable in a specified chemical environment. Metabolic modeling has been applied to analyze the connectivity and behavior of the simple metabolic network included in Gill's minimal set of 206 genes [44]. This work found the simple network to function successfully as a concerted whole and behave similarly to natural metabolic networks.…”
Section: Model-driven Design Of a Minimal Metabolismmentioning
confidence: 99%
“…Using stoichiometric analysis of elementary flux modes (EFM), Gabaldón et al (2007) showed that 49 out of 50 enzymatic steps of a minimalist metabolism were essential for maintaining the stoichiometric coherence. Thus, this metabolic network had only one redundant chemical transformation revealing its true minimalist character.…”
Section: A Hierarchy Of Minimal Cells Based On Metabolic Complexitymentioning
confidence: 99%
“…However, from the metabolic point of view, our CMG defined just one of many possible minimal metabolic charts, which would depend on environmental conditions. Gabaldón et al (2007Gabaldón et al ( , 2008 further analyzed this particular minimalist metabolism, using graphtheory based methods and stoichiometric analysis.…”
Section: The Minimal Gene Set For Life Can Be Approached By Comparatimentioning
confidence: 99%